2022
DOI: 10.1038/s41598-022-13916-5
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of peripherally inserted central catheter-related venous thromboembolism in patients with hematological malignancies

Abstract: This study aimed to explore the risk factors of peripherally inserted central catheter (PICC)-related venous thromboembolism (CRT) in patients with hematological malignancies and the predictive ability of the thrombotic risk assessment models (RAMs). The clinical data of the 117 eligible patients with hematological neoplasms at Mianyang Central Hospital with PICC from May 2018 to May 2020 were analyzed in this retrospective study. Thrombosis risk scores were calculated in patients with image-confirmed PICC-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In critically ill children, the reported prevalence of CRT varies from 1-9% [19], and, among different cancer centers, the venous thromboembolism rates, in patients with acute leukemia, range from < 1-81% [17][18][19][20]30]. Jaffray et al found a CRT incidence rate of 9%±1.4%[26], while a higher incidence (16.2%) was observed in 117 adults with hematologic malignancies [31]. The CRT incidence rate was quite similar (2.6%; 0.2/1,000 PICC days) in a monocentris retrospective study, including 612 PICCs/483 adults, treated in our institute [10].…”
Section: Discussionmentioning
confidence: 99%
“…In critically ill children, the reported prevalence of CRT varies from 1-9% [19], and, among different cancer centers, the venous thromboembolism rates, in patients with acute leukemia, range from < 1-81% [17][18][19][20]30]. Jaffray et al found a CRT incidence rate of 9%±1.4%[26], while a higher incidence (16.2%) was observed in 117 adults with hematologic malignancies [31]. The CRT incidence rate was quite similar (2.6%; 0.2/1,000 PICC days) in a monocentris retrospective study, including 612 PICCs/483 adults, treated in our institute [10].…”
Section: Discussionmentioning
confidence: 99%
“…To assess the risk of thrombosis in patients, various scoring scales have been developed, such as the Caprini scale, Padua scale, modified Wells scale, revised Geneva scale, and Michigan risk score [7][8][9][10][11] . Among these, the Caprini scale is the most commonly used and regarded as the most accurate for many patients 12,13 . Orthopedic surgery patients are at a heightened risk of thrombosis, prompting many specialists to establish guidelines for prevention.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[7][8][9][10][11] Among these, the Caprini scale is the most commonly used and regarded as the most accurate for many patients. 12,13 Orthopaedic surgery patients are at a heightened risk of thrombosis, prompting many specialists to establish guidelines for prevention. These guidelines typically advise on medication, devices, and other preventative measures to minimize the risk of DVT.…”
Section: Introductionmentioning
confidence: 99%